2017
DOI: 10.3892/or.2017.5577
|View full text |Cite
|
Sign up to set email alerts
|

TXNIP overexpression suppresses proliferation and induces apoptosis in SMMC7221 cells through ROS generation and MAPK pathway activation

Abstract: Abstract. Thioredoxin binding protein (thioredoxin-interacting protein, TXNIP), known as vitamin D3 increase protein 1, has been identified as a tumor suppressor in various cancers such as pancreatic, breast, lung and thyroid cancer. However, the role of TXNIP in hepatocellular carcinoma cell proliferation and apoptosis remains unknown. In this study, we first used qRT-PCR, western blotting and immunohistochemistry to compare the expression of TXNIP between hepatocellular carcinoma tissues and tumor-adjacent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
(39 reference statements)
1
35
1
Order By: Relevance
“…S1). TXNIP is involved in redox regulation and acts as a negative regulator of glycolysis [23,[40][41][42][43]. To assess whether BRG1 regulated a STAT3 pathway leading to TXNIP upregulation, lysates from control (scrambled shRNA), and BRG1-KD GBM6 and X16 GICs were prepared and immunoblotted.…”
Section: Brg1 Regulates An Stat3/txnip Pathwaymentioning
confidence: 99%
“…S1). TXNIP is involved in redox regulation and acts as a negative regulator of glycolysis [23,[40][41][42][43]. To assess whether BRG1 regulated a STAT3 pathway leading to TXNIP upregulation, lysates from control (scrambled shRNA), and BRG1-KD GBM6 and X16 GICs were prepared and immunoblotted.…”
Section: Brg1 Regulates An Stat3/txnip Pathwaymentioning
confidence: 99%
“…In recent studies, exposure to SiONPs induces an inflammatory response in human lung cells, and this effect is associated with the elevation of the MAPKs signaling pathway [17,18]. In addition, thioredoxin-interacting protein (TXNIP) plays a role as an oxidative stress activator by decreasing the antioxidant activity of thioredoxin (TRX) [19]. A previous study has shown that the downregulation of TXNIP ameliorates inflammatory responses by inhibiting the MAPKs pathway in mice [20].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of TXNIP expression was reported to be associated with the development of some solid tumors [12]. In the breast, high expression of TXNIP was reported in normal breast tissues [13] and showed reduced immunointensity in invasive tumors [14]. Ectopic expression of TXNIP in the breast cancer cell line MCF-7 drives cells to undergo senescence, accompanied by increased reactive oxygen species release.…”
Section: Introductionmentioning
confidence: 99%